2023
DOI: 10.1590/1414-431x2023e12713
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability in long-term culture of human adipose-derived mesenchymal stromal cells

Abstract: Mesenchymal stromal/stem cells stem (MSC) have been widely studied due to their great potential for application in tissue engineering and regenerative and translational medicine. In MSC-based therapy for human diseases, cell proliferation is required to obtain a large and adequate number of cells to ensure therapeutic efficacy. During in vitro culture, cells are under an artificial environment and manipulative stress that can affect genetic stability. Several regulatory agencies have established guidelines to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…140 There is an association between genomic instability (DNA damage and chromosome changes) and long cell culture or high passage numbers, which should be taken into account in cell therapies to guarantee the highest possible safety. 141 The increase in cell immunogenicity after MSC transplantation may constitute another concern for clinical applications.…”
Section: Safety Of Mesenchymal Stem Cell-based Therapymentioning
confidence: 99%
“…140 There is an association between genomic instability (DNA damage and chromosome changes) and long cell culture or high passage numbers, which should be taken into account in cell therapies to guarantee the highest possible safety. 141 The increase in cell immunogenicity after MSC transplantation may constitute another concern for clinical applications.…”
Section: Safety Of Mesenchymal Stem Cell-based Therapymentioning
confidence: 99%
“…The clonal evolution of somatic TP53 mutations and MDM2 amplification have been observed in newly created chondrosarcoma cell lines grown as tumor spheres [6]. A temporal analysis of an adipose-derived mesenchymal stromal cell line highlighted genetic divergence, but only with the fifth passage, demonstrating the culture stability of DNA in the first few passages [7]. One study showed the stability of gene expression and copy number profiles in adult glioblastoma cell lines [8].…”
Section: Introductionmentioning
confidence: 99%